Synthesis of alpha-ketoamides using potassium superoxide (KO2) as an oxidizing agent - Vasudevan, N.; Routholla, Ganesh; Illa, Giri Teja; Reddy, D. Srinivasa (Tetrahedron, 2020)
A simple and convenient method for the synthesis of alpha-ketoamides by the oxidation of aryl acetamides using potassium superoxide (KO2) as an oxidizing agent is disclosed here. The scope of the developed method is successfully tested with fifteen substrates. In addition, the utility of method has been demonstrated by synthesizing an orexin receptor antagonist, a medicinally interesting compound. (C) 2020 Published by Elsevier Ltd.
Keywords: alpha-Ketoamide; Orexin receptor; Oxidation; Potassium superoxide (KO2)

Ready access to benzodiazocines from tryptamines: a druggable scaffold toward antiviral agents - Saranya, N. Sathya Sai; Choudhury, Rahul; Routholla, Ganesh; Supekar, Prathmesh R.; R, Nandhakumaar; Martin, Alna Kuriyickal; Muruganandham, Renuga Devi; Kumar, Bokara Kiran; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2025)
Herein we report the first synthesis of the proposed structure of a benzodiazocine natural product, peganutonin A. Considering the druggable nature of benzodiazocine and its limited exploration in the field of medicinal chemistry, we generalized the approach and created a library of compounds useful for various biological activities. Key steps in present approach include tryptamine cyclization facilitated by tert-butyl hypochlorite and cleavage of the fused indole ring using ozonolysis. Preliminary screening of the synthesized compounds resulted in potent antiviral compounds against the SARS-CoV-2 virus.
Keywords: Benzodiazocine; drug discovery; Indole cleavage; Lipinski's rule of Five; SARS-CoV-2 inhibition; Tryptamine